Trifluoromethyl fluoroformyl trioxicarbonate, CF3OC(O)OOOC(O)F: The first nonsymmetric acyl trioxide - Manetti, Martin Diego (2009)
This paper reports for the first time the synthesis and characterization of trifluoromethyl fluoroformyl trioxicarbonate, CF3OC(O)OOOC(O)F. The new trioxide is obtained from the gas-phase photolytic reaction of CF 3C(O)OC(O)CF3and FC(O)C(O)F at 223-228 K. It is a very thermally labile molecule that decomposes at room temperature by rupture of either of the CF3OC(O)O-O-OC(O)F bonds. These bonds are nonequivalent, and a branching ratio of 0.8 for fragmentation through the CF3OC(O)OO-OC(O)F bond was obtained. Unambiguous identification was possible through reaction of the trioxide with an excess of NO2. Potential-energy surfaces (PES) of the different rotamers were studied by the B3LYP/6-311+G* method, and analysis of the IR frequency of the possible mixture of rotamers agrees excellently with the experimental IR spectrum. This molecule is the first nonsymmetric acyl trioxide reported in the literature.